Magija in magično zdravljenje v pripovednem izročilu in ljudsko zdravilstvo danes - Kropej, Monika (Etnolog. Nova vrsta (Ljubljana), 2000)
The article present magical practices and folk medicine as preserved in folk traditions. The second part of the article is based on the practice of folk medicine in Slovenji Plajberg and brings a comparison with stories on magical treatment in Rosenthal in Carinthia, recorded in the first half of the 20th century.
Keywords: ethnology; etnologija; ljudska medicina; verovanje; zdravilstvo